Interactions of Desmethoxyyangonin, a Secondary Metabolite from Renealmia alpinia, with Human Monoamine Oxidase-A and Oxidase-B. (24th August 2017) - Chaurasiya, Narayan D.; León, Francisco; Ding, Yuanqing; Gómez-Betancur, Isabel; Benjumea, Dora; Walker, Larry A.; Cutler, Stephen J.; Tekwani, Babu L.
Abstract : Renealmia alpinia (Zingiberaceae), a medicinal plant of tropical rainforests, is used to treat snakebites and other injuries and also as a febrifuge, analgesic, antiemetic, antiulcer, and anticonvulsant. The dichloromethane extract of R. alpinia leaves showed potent inhibition of human monoamine oxidases- (MAOs-) A and B. Phytochemical studies yielded six known compounds, including pinostrobin 1, 4′-methyl ether sakuranetin 2, sakuranetin 3, pinostrobin chalcone 4, yashabushidiol A 5, and desmethoxyyangonin 6 . Compound 6 displayed about 30-fold higher affinity for MAO-B than MAO-A, with Ki values of 31 and 922 nM, respectively. Kinetic analysis of inhibition and equilibrium-dialysis dissociation assay of the enzyme-inhibitor complex showed reversible binding of desmethoxyyangonin 6 with MAO-A and MAO-B. The binding interactions of compound 6 in the active site of the MAO-A and MAO-B isoenzymes, investigated through molecular modeling algorithms, confirmed preferential binding of desmethoxyyangonin 6 with MAO-B compared to MAO-A. Selective reversible inhibitors of MAO-B, like desmethoxyyangonin 6, may have important therapeutic significance for the treatment of neurodegenerative disorders, such as Parkinson's disease and Alzheimer's disease.